The Jilakata: Notes on the political system of the Aymara - INDICEP, INDICEP (1973)
In the Aymara populations, the peasants are grouped in a certain ayllu and this has its communal authority, the Jilakata, a native authority that complies with the customs of our Aymara ancestors. Within the ayllu, the Julakata is the highest authority whom everyone must respect.